Literature And Translation For Effective Teaching In Secondary School English Classes Of Arabic Students - Chaabane, Bechir (Ijaz Arabi Journal of Arabic Learning, 2024)
This paper specifies that involving literary texts in the teaching class, especially in the context of the Arab world, is detrimental. Since major troubles are attributed to the negative transfer due to linguistic differences between Arabic and English, literary texts can be corrective and therapeutic. They provide the required contexts to socialize young learners with the language in use. The pragmatic function of language dictates much more than contrived examples to come to terms with its intended meaning. Literature-based teaching makes learning more natural than artificial through authentic language and make-believe situations. The flip side is that the language of literary texts may be troublesome, but this inconvenience can be wiped away by literary translation. According to the questionnaire respondents regarding the inclusion of translation in the teaching class, it can be applied without demur since Arab learners mechanically translate explicitly or silently throughout the lesson. As such, the blend of literature and English language teaching with the help of literary translation can be adequate pedagogic support for secondary school Arab learners.